Efficacy and safety of Coccinia grandis (L.) Voigt on blood glucose and lipid profile: An updated systematic review and meta-analysis - Wiraphol Phimarn; Chatmanee Taengthonglang; Bunleu Sungthong (Shahrekord University of Medical Sciences, 2024)
Introduction: Coccinia grandis has been shown to improve blood glucose and lipids. The results of earlier clinical studies on the effects of C. grandis on blood sugar and lipid profile are debatable. This meta-analysis aimed to evaluate, using randomized controlled trials (RCTs), the effects of consuming C. grandis on lipid profiles and blood glucose levels. Methods: Thai and English articles by two independent authors were searched in PubMed, ScienceDirect, Scopus, and ThaiJo up to November 2023 for a systematic review. The keywords were developed based on MeSH terms as follows: (Coccinia grandis OR Coccinia cordifolia OR Coccinia indica) AND (fasting blood glucose OR FBS OR fasting plasma glucose OR FPG OR HbA1C OR postprandial glucose OR PPG OR lipid profile OR low-density lipoprotein OR LDL OR high-density lipoprotein OR HDL OR total cholesterol OR TC OR triglyceride OR TG). The Laird and DerSimonian random-effect model was used to pool the findings. Seven trials with 595 individuals and 1-90-day treatments were included. Results: The combined data revealed a noteworthy decline in fasting blood sugar (FBS); standardized mean difference (SMD) by -1.99 mg/dL (P<0.001), 1-hour postprandial glucose (PPG) by -0.99 mg/dL (P<0.001), 2-hour PPG by -0.69 mg/dL (P=0.004) and triglycerides (TG) by -0.46 mg/dL (P=0.001). However, there were no significant differences in hemoglobin A1C (HbA1C), low-density lipoprotein (LDL), high-density lipoprotein (HDL), and total cholesterol (TC). No major intervention side effects were recorded. Conclusion: Our investigation found that C. grandis reduced FBS, PPG, and TG. The treatment's long-term advantages and safety are unknown.